Bagasse-Based Cellulose Nanocrystal–Magnetic Iron Oxide Nanocomposite for Removal of Chromium (VI) from Aqua Media - Evans Suter; Hilary Rutto; Tumisangs Seodigeng; Lewis Kiambi; Wesley Omwoyo (Engineering Proceedings)
This research developed a low-cost nano-bio-adsorbent using sugar cane bagasse-based nanocrystals incorporated with magnetic iron oxide nanoparticles (CNCs-MIONPs). The adsorbent demonstrated excellent Cr(VI) adsorption efficiency at an optimal pH of 2.0, an initial concentration of 0.5 mg/L, and a contact time of 90 min with a shaking rate of 250 rpm, achieving a removal efficiency of 91.78%. The increased surface area, smaller particle size, and the nanocomposite’s active sites facilitated chromium species’ immobilisation, enhancing chromate ion removal. The adsorption process involved chemisorption, where valence forces such as electron sharing or exchange occur between the adsorbate and sorbent. The modified CNCs-MIONPs showed improved sorption efficiency, suggesting potential applications in water treatment plants, both for domestic and industrial wastewater.